Efficient Removal of Copper and Cadmium from Contaminated Soil Utilizing Electrokinetic Process - Muhammad Saleem (Yanbu Journal of Engineering and Science, 2021)
Present manuscript demonstrates the efficient removal of copper and cadmium from contaminated soil utilizing electrokinetic process. The results of systematic bench-scale study on improved extraction of copper and cadmium shows the suitability of process to decontaminate low permeable soil. The influence of operating parameters such as electrode material, soil pH, current density, soil temperature, inter-electrode spacing and initial soil moisture content on the decontamination performance is investigated. Study revealed that, removal of copper and cadmium reached to 89.4% and 62.7% respectively while using titanium electrodes. Removal efficiency improved with the increase in current density, soil temperature and initial soil moisture content. About 74.5% of copper removal achieved within 20 hours at soil temperature of 35°C and current density was kept at 9.3 mA/cm^2^. During this study, soil pH decreased from 6.7 to 2.4 near anode and reached up to 12.3 near cathode resulting in augmented metal removal. An improvement of 33% in removal efficiency observed when moisture content increased from 45% to 73%. Rate of metal removal increased as the inter-electrode spacing decreased to 15 cm, which demonstrated the highest copper removal at a current density of 9.3 mA/cm^2^. The maximum energy consumption found to be 5.2 kWh/m^3^ of soil volume demonstrated the economy of process, which can be scaled up at cleanup sites.